2022
DOI: 10.1007/s10163-022-01476-9
|View full text |Cite
|
Sign up to set email alerts
|

Thiourea leaching of gold from processed municipal solid waste incineration residues

Abstract: Incineration is one of the key technologies in disposal of municipal waste, which produces municipal solid waste incineration (MSWI) residues with high valuable metal contents. The recycling strategy for the MSWI residues is typically focused on the recovery of scrap metals yielding processed municipal solid waste incineration residues (PIR) as the main byproduct. However, the PIR still contains valuable metals, particularly gold, which cannot be extracted by conventional methods. Here, we evaluated the feasib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 95 publications
(150 reference statements)
0
2
0
Order By: Relevance
“…The present study was optimized as per Jing-ying et al, which contained 40 mL of a mixture solution containing 24 g/L thiourea, 0.6% Fe 3+ , and 0.5 mol/L sulfuric acid for pH adjustment (pH = 2) for heating at 25 °C to extract Au, Ag, and Cu . Mild oxidants such as Fe 3+ and acidic medium (pH = 1–2) help in maintaining the stability of thiourea and improving the extraction efficiency of gold. ,,, The stirring speed was kept at 150 rpm to improve agitation and mass transfer . However, it was found that stirring speed played no major role in accelerating gold extraction using acid thiourea solution. , In the current leaching experiment, 1 g of the solid residue is taken from our previous study .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study was optimized as per Jing-ying et al, which contained 40 mL of a mixture solution containing 24 g/L thiourea, 0.6% Fe 3+ , and 0.5 mol/L sulfuric acid for pH adjustment (pH = 2) for heating at 25 °C to extract Au, Ag, and Cu . Mild oxidants such as Fe 3+ and acidic medium (pH = 1–2) help in maintaining the stability of thiourea and improving the extraction efficiency of gold. ,,, The stirring speed was kept at 150 rpm to improve agitation and mass transfer . However, it was found that stirring speed played no major role in accelerating gold extraction using acid thiourea solution. , In the current leaching experiment, 1 g of the solid residue is taken from our previous study .…”
Section: Resultsmentioning
confidence: 99%
“…32,33,40,41 The stirring speed was kept at 150 rpm to improve agitation and mass transfer. 42 However, it was found that stirring speed played no major role in accelerating gold extraction using acid thiourea solution. 43,44 In the current leaching experiment, 1 g of the solid residue is taken from our previous study.…”
Section: Chemical Stability Testmentioning
confidence: 99%